Implications of the Free Curriculum and PMM Digitalization Policy on the Decline of Teacher and Student Quality (A Study using Max Horkheimer's Critical Social Theory Approach) - Ibrahim Sudirman; Syamsu A. Kamaruddin; Arlin Adam (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This study aims to gather information on the decline in the quality of teachers and students as a result of the Free Curriculum policy, using Max Horkheimer's critical social theory approach. The methodology employed is qualitative descriptive, which will elaborate on data through descriptive statements. Data is obtained through a literature review of previous studies and informants who have implemented this Free Curriculum policy.The findings of this research indicate that the Free Curriculum is part of modernity in the educational aspect. Modernity is a state where all traditionally oriented societal systems are released into an order that implies rationality. The essence of modernization fundamentally encourages embracing change towards improvement in line with the capacity of the surrounding community conditions. Differentiated learning poses new problems and burdens for teachers due to time constraints. The standards to be achieved become biased and unclear. The impact of this policy is that students experience a decline in the quality of understanding the material because it is challenging to meet achievement standards maximally due to diversity in potential and interests. Teachers are not maximally able to provide standardized teaching but are more focused on organizing and designing strategies for this diversity.The role of teachers as facilitators allows limited room to maximize the inculcation of values. Discrimination against teachers through the "teacher mover" program resulting from the Free Curriculum policy has an impact on the opportunities provided, creating discrimination and generating barriers and comparisons between participating and non-participating teachers.